Relationship between head of department leadership styles and lecturers job satisfactions in Nigerian public universities - Sakiru, Oladipo Kolapo; Othman, Jamilah; Silong, Abu Daud; Kareem, Salami Dada; Oluwafemi, Awotayo Olagoke; Yusuf, Gafar OLanrewaju (Canadian Center of Science and Education, 2014)
The Study, relationship between leadership styles and job satisfaction among the head of department and lecturers of Nigerian public universities is definitely a problem of an accelerating importance towards the higher learning institution within their preparation to complete their mission to become a first class university.A highly effective leadership style, along with a reliable labor force appeared to become a decisive importance for any university to have the ability to compete in quality and also to accompany the changes. At the moment, the empirical linkages between the head of department leadership styles and job satisfaction among lecturers in Nigerian public universities aren't fully established by past researchers.Therefore, it is the aim of this study to investigate the relationship between the selected independent variables; leadership styles (transformational, transactional, lasseir-faire) and job satisfaction as the dependent variables, determines the common leadership style that is commonly used by the head of the department, and determines the level of job satisfaction among the lecturers. The research design was descriptive correlational study and data were collected employing questionnaires. The study utilized simple random sampling methods to select 217 lecturers with the response rate of 91.7% from the population of Nigerian lecturers studying at three research universities in Malaysia.The findings showed that lecturers job satisfaction is high and also the descriptive statistics revealed that the most commonly used leadership styles among the head of department of Nigeria public university is transformational leadership styles, with the highest mean of 3.9032. The result obtained from the correlational analyses revealed that there is a significant relationship between leadership styles of the head of department and lecturers job satisfaction in public universities in Nigeria. The present study contributes useful information for educational leaders and researchers in the field of human resource development.